2016
DOI: 10.3109/00365521.2016.1138239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the therapeutic efficacy and safety between tacrolimus and infliximab for moderate-to-severe ulcerative colitis: a single center experience

Abstract: Tac and IFX may be equally efficacious for the induction and maintenance of remission in patients with UC while minor adverse events are more frequent with the former treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Serum albumin and CRP levels at baseline were not statistically different between groups. Nuki et al [11] reported in their retrospective study of 46 patients with moderate to severe UC the clinical remission rate after 10 weeks was 76% and 67% in the IFX and Tac groups, respectively. They reported CRP levels at baseline were not statistically different between groups, but serum albumin levels were not discussed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Serum albumin and CRP levels at baseline were not statistically different between groups. Nuki et al [11] reported in their retrospective study of 46 patients with moderate to severe UC the clinical remission rate after 10 weeks was 76% and 67% in the IFX and Tac groups, respectively. They reported CRP levels at baseline were not statistically different between groups, but serum albumin levels were not discussed.…”
Section: Discussionmentioning
confidence: 95%
“…Tacrolimus (Tac), a calcineurin inhibitor that has a mechanism of action similar to CsA, also has therapeutic efficacy for moderate to severe UC [7,8]. Several retrospective studies showed IFX and Tac had equal efficacy for moderate to severe UC [9][10][11]. These studies were retrospective and therefore the background characteristics of the patients were not randomized.…”
Section: Introductionmentioning
confidence: 99%
“…Renal dysfunction was also observed in the TAC group; however, creatinine levels returned to the normal range after reducing the dose of TAC [9]. IFX therapy was temporarily ceased in several patients with infections such as pneumonia and herpes zoster [8].…”
Section: Safety and Adverse Eventsmentioning
confidence: 94%
“…In this review, TAC was switched to azathioprine at 3 months in the majority of patients. However, indeed, a few patients received TAC for more than 3 months at the physicians' discretion [7,9,10]. Nevertheless, the long-term efficacy of TAC as maintenance therapy could not be properly evaluated because of a small sample size.…”
Section: Long-term Efficacy (Maintenance Efficacy)mentioning
confidence: 99%
“…Figure 1 shows the flow diagram which describes the reasons for citations exclusion. Finally, 22 studies (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)28,30,32,33) that fulfilled eligibility criteria were included. Only two studies were randomized controlled trials (24,25) (Ogata 2006 and Ogata 2012); these were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%